Method for manufacturing electrode laminate, electrochemical device, and method for manufacturing electrochemical device

By introducing porous metal layer and sheet collector into the electrode laminate of all solid batteries, the problem of unstable contact between the electrode laminated body and the conduction path is solved, and electrochemical components with low internal resistance and small deviation are realized , prevents short circuits and improves the reliability of the battery.

CN119301815APending Publication Date: 2025-01-10MAXELL LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202380043650.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-28
Filing Date
2023-06-23
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

In all-solid batteries, the contact between the electrode laminate and the conduction path is unstable, resulting in high internal resistance and large deviations, which easily lead to short-circuit problems.

Method used

An electrode laminate structure with an isolation layer is adopted, wherein at least one electrode surface is arranged with a porous metal layer, and a sheet-like current collector is formed by compressing the porous substrate to ensure good contact and homogenization of the electrode with the conduction path. Conduct.

Benefits of technology

Electrochemical components with low internal resistance and reduced deviation are realized to prevent short circuits and improve the reliability and stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119301815A_ABST
    Figure CN119301815A_ABST
Patent Text Reader

Abstract

Provided are an electrochemical element having low internal resistance and reduced variation, a method for manufacturing an electrode laminate capable of preventing the occurrence of a short circuit when assembling the electrochemical element, an electrochemical element using the electrode laminate manufactured by the manufacturing method, and a method for manufacturing the electrochemical element. In an electrochemical element according to a first embodiment of the present invention, a porous metal layer is interposed between an electrode laminate comprising a first electrode, a separation layer, and a second electrode and a conduction path of an exterior body, and the electrode laminate is pressed against the porous metal layer by a pressing means. In a second embodiment of the present invention, when producing an electrode laminate provided with a first electrode and / or a second electrode having an electrode mixture layer and a sheet-shaped current collector, the relationship between the thickness s of the porous base material before compression, the thickness t of the portion of the porous base material facing the electrode mixture layer after compression, the thickness a of the electrode mixture layer, and the thickness b of the separator layer satisfies s-tlt. The amount of compression of the porous base material is adjusted so as to satisfy a + b, thereby forming a sheet-like current collector.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for producing an electrode stack capable of preventing the occurrence of a short circuit when assembling an electrochemical element, an electrochemical element using the electrode stack produced by the production method, a production method thereof, and an electrochemical element having a low internal resistance and reduced variation therein. Background Art

[0002] In recent years, with the development of portable electronic devices such as mobile phones and notebook personal computers, and the practical application of electric vehicles, there is a demand for small and lightweight batteries with high capacity and high energy density.

[0003] At present, in lithium batteries that can meet this requirement, especially lithium ion batteries, the positive electrode active material uses lithium-containing composite oxides such as lithium cobalt oxide (LiCoO2) and lithium nickel oxide (LiNiO2), the negative electrode active material uses graphite, etc., and an organic electrolyte containing an organic solvent and a lithium salt is used as the non-aqueous electrolyte.

[0004] Furthermore, as the application equipment of lithium ion batteries further develops, lithium ion batteries are required to have a longer life, higher capacity, and higher energy density, and lithium ion batteries with longer life, higher capacity, and higher energy density are also required to have higher reliability.

[0005] However, the organic electrolyte used in lithium-ion batteries contains an organic solvent as a flammable substance, so when the battery is short-circuited or other abnormal conditions occur, the organic electrolyte may generate abnormal heat. In addition, with the high energy density of lithium-ion batteries in recent years and the increasing trend of the amount of organic solvent in the organic electrolyte, the reliability of lithium-ion batteries is further required.

[0006] Under the above situation, research is also underway on all-solid lithium batteries (all-solid batteries) that do not use organic solvents. All-solid batteries use a molded solid electrolyte that does not use organic solvents to replace the conventional organic solvent-based electrolytes, and there is no need to worry about abnormal heating of the solid electrolyte, so they are highly safe.

[0007] In addition, all-solid-state batteries are not only highly safe, but also highly reliable and environmentally resistant, and have a long lifespan. Therefore, they are expected to be maintenance-free batteries that can contribute to social development while also continuously contributing to peace of mind and safety. By providing all-solid-state batteries to society, we can contribute to the achievement of Goal 3 (Ensure healthy lives and promote well-being for all at all ages), Goal 7 (Ensure access to affordable, reliable, sustainable and modern energy for all), Goal 11 (Achieve inclusive, safe, resilient (risk-resistant) and sustainable cities and human settlements), and Goal 12 (Ensure sustainable production and consumption patterns) among the 17 goals of the Sustainable Development Goals (SDGs) set by the United Nations.

[0008] However, in batteries such as all-solid batteries, flat batteries such as coin-shaped batteries and button-shaped batteries are known. In such flat batteries, an outer body formed by sandwiching a gasket between an outer can and a sealing can and crimping the open end of the outer can inward is used. Moreover, in batteries such as all-solid batteries having an electrode (granular electrode) composed of a molded body of an electrode mixture containing an active material, the outer can and the sealing can are usually used as a conduction path from the inside of the battery to the outside, and the granular electrode is contacted with the conduction path, so that the outer can and the sealing can function as a pair of electrode terminals, respectively.

[0009] However, when a granular electrode is in contact with the conductive path, the conductive connection between the electrode and the conductive path cannot be sufficiently ensured due to vibration, volume change of the electrode during charge and discharge, etc., and the internal resistance of the battery is likely to increase.

[0010] Furthermore, when the granular electrode is brought into contact with the conductive path, the degree of contact between the granular electrode and the conductive path in each battery may vary due to variations in the stacking thickness of the granular electrode and the size of the outer can, and the internal resistance of the battery may increase or its variation may increase, thereby causing a problem in that the variation in the discharge load characteristics of the battery may also increase.

[0011] On the other hand, a technology for reducing the internal resistance in a battery having a conductive path as described above has also been proposed. For example, Patent Document 1 discloses a flat all-solid battery, which is configured by arranging a conductive porous member having a flexible shape of graphite between a stack formed by stacking a positive electrode, a solid electrolyte layer and a negative electrode and the inner bottom surface of an outer can or an inner bottom surface of a sealing can, thereby maintaining good contact with the electrode stack and the battery container, and ensuring excellent conductivity. In the case where a porous member of graphite is arranged between the electrode stack and the battery container, the electrode stack and the porous member are pressed when the battery is assembled, and the porous member can be kept in a compressed state. Therefore, if the thickness of the porous member is adjusted correspondingly to the deviation of the thickness of the electrode stack, the deviation of the height of the outer material, etc., an excellent conductive state can be achieved between the electrode stack and the battery container.

[0012] Prior art literature

[0013] Patent Literature

[0014] Patent Document 1: International Publication No. 2020 / 066323 Summary of the invention

[0015] Problems to be solved by the invention

[0016] However, as described in Patent Document 1, when a porous formed sheet of graphite is arranged between the electrode stack and the battery container, the conductive state between the electrode stack and the battery container can be improved by the pressing force of the sheet. However, there is room for further research to achieve a better conductive connection including the material of the collector and to reduce the deviation of the internal resistance in each battery.

[0017] In addition, as described in Comparative Example 2 of Patent Document 1, when a porous sheet with a large deformation amount that is easily compressed when pressed, or a porous sheet with a high porosity such as a foamed metal porous body is used as a conductive porous sheet, if the position of the electrode stack and the porous sheet is shifted when assembling the battery, the following problems may occur.

[0018] When the electrode stack and the porous sheet are stacked offset and the peripheral end of the porous sheet is pressed as a whole in a state where the peripheral end of the porous sheet protrudes from the end of the electrode stack, the portion facing the electrode stack is compressed and reduced in thickness, whereas the peripheral end of the porous sheet protruding from the end of the electrode stack is not compressed and remains. Therefore, depending on the original thickness of the porous sheet and the amount of compression, the height of the peripheral end of the porous sheet reaches the electrode located on the opposite side of the electrode stack from the porous sheet, and there is a risk that the two electrodes will be short-circuited via the peripheral end of the porous sheet.

[0019] In particular, when at least a portion of the porous sheet is buried in the electrode, the end portion of the porous sheet (the side facing the counter electrode) is close to the counter electrode, so the above-mentioned problem is more likely to occur.

[0020] The present invention is completed in view of the above situation, and its purpose is to provide an electrochemical element with low internal resistance and reduced deviation. In addition, another object of the present invention is to provide a method for manufacturing an electrode stack that can prevent the occurrence of a short circuit when assembling an electrochemical element, an electrochemical element using an electrode stack manufactured by the manufacturing method, and a manufacturing method thereof.

[0021] Means for solving problems

[0022] A first aspect of the present invention is an electrochemical element, characterized by comprising an electrode laminate and an exterior body. The electrode laminate has a first electrode, a second electrode, and a separator layer interposed between the first electrode and the second electrode, and the electrode laminate is sealed inside the exterior body; at least one of the first electrode and the second electrode of the electrode laminate has a current collector on the surface on the opposite side of the separator layer and is electrically connected to a porous metal layer disposed on the surface of the current collector; the electrochemical element has a pressing unit for pressing the electrode laminate against the porous metal layer; the exterior body has a conduction path leading from the inside to the outside, and the conduction path is electrically connected to the porous metal layer.

[0023] In addition, a second aspect of the present invention includes a method for manufacturing an electrode laminate, which is a method for manufacturing an electrode laminate having a first electrode, a second electrode, and a separator layer interposed between them. The method is characterized in that at least one of the first electrode and the second electrode has an electrode binder layer and a sheet-like current collector disposed on the surface of the electrode binder layer; the manufacturing method has a step of forming the sheet-like current collector by compressing a porous substrate in the thickness direction. When the thickness of the porous substrate before compression is set as s, the thickness of the compressed portion of the porous substrate opposite to the electrode binder layer is set as t, the thickness of the electrode binder layer is set as a, and the thickness of the separator layer is set as b, the compression amount of the porous substrate is adjusted so as to satisfy s - t < a + b.

[0024] Furthermore, the second aspect of the present invention also includes an electrochemical element, characterized by having an exterior body and an electrode laminate sealed inside the exterior body, and the electrode laminate is manufactured by the method for manufacturing an electrode laminate of the present invention.

[0025] In addition, the second aspect of the present invention also includes a method for manufacturing an electrochemical element, characterized by being a method for manufacturing an electrochemical element having an exterior body and an electrode laminate sealed inside the exterior body. As the electrode laminate, an electrode laminate manufactured by the method for manufacturing an electrode laminate of the present invention is used.

[0026] Advantages of the Invention

[0027] According to the first aspect of the present invention, an electrochemical element with low internal resistance and reduced deviation thereof can be provided.

[0028] In addition, according to the second aspect of the present invention, when a sheet-like current collector formed by compressing a porous substrate in the thickness direction is disposed on the surface of at least one electrode of the electrode laminate used in the assembly of the electrochemical element, even if the position of the current collector is shifted, the occurrence of an internal short circuit can be prevented. Description of the Drawings

[0029] [ Figure 1 ] is a cross-sectional view schematically showing an example of an electrochemical element of the first embodiment of the present invention.

[0030] [ Figure 2 ] is a cross-sectional view schematically showing the main parts of an example of an electrode stack produced by the production method of the present invention.

[0031] [ Figure 3 ] is a cross-sectional view schematically showing an example of an electrochemical element of the present invention having an electrode stack manufactured by the manufacturing method of the present invention. DETAILED DESCRIPTION

[0032] Figure 1 2 is a longitudinal cross-sectional view schematically showing an example of the electrochemical device according to the first embodiment of the present invention. Figure 1 The electrochemical element 10 shown has an electrode stack 20 including a first electrode 21 , a second electrode 22 , and a separator 23 interposed therebetween, and the electrode stack 20 is enclosed in an outer casing formed of an outer container 60 and a cover 70 .

[0033] On the lower surface of the outer container 60 in the figure, external terminals 80 and 90 for electrical connection to a device to which the electrochemical element 10 is applied are provided. In addition, the external terminal 80 is electrically connected to the first electrode 21 in the electrode stack 20 through the conductive path 81. Furthermore, the external terminal 90 is electrically connected to the second electrode 22 in the electrode stack 20 through the lead 40 and the conductive path 91.

[0034] The first electrode 21 constituting the electrode stack 20 includes an electrode mixture layer (electrode mixture molded body) 211 and a current collector 212. The second electrode 22 constituting the electrode stack 20 includes an electrode mixture layer (electrode mixture molded body) 221 and a current collector 222.

[0035] When the stacked electrode body 20 has a solid electrolyte layer as the separator 23, for example, only the stacked electrode body 20 is sealed in the outer package. On the other hand, when the stacked electrode body 20 has a separator as the separator 23, an electrolyte (not shown) is sealed in the outer package together with the stacked electrode body 20.

[0036] Furthermore, the porous metal layer 30 is disposed on the surface of the current collector 212 of the first electrode 21 (the surface opposite to the electrode mixture layer 211 ), and the first electrode 21 is in contact with the current collector 212 to be electrically connected to the porous metal layer 30 .

[0037] Since the porous metal layer has pores and is made of metal, it can be easily plastically deformed by applying force in the thickness direction. Thus, when forming an electrochemical element, the porous metal layer is compressed and deformed by inserting the electrode stack into the outer body in a manner of pressing the electrode stack onto the porous metal layer (the porous body made of metal constituting it), so that one of the first and second electrodes constituting the electrode stack can be in good contact with the collector, and in addition, the degree of conduction between the porous metal layer and the electrode stack in each electrochemical element when manufacturing multiple electrochemical elements can be homogenized. In the first embodiment of the present invention, through these effects, an electrochemical element with low internal resistance and reduced deviation of each internal resistance can be provided.

[0038] The porous metal layer in the first embodiment of the present invention can be composed of a porous body composed of a metal that does not adversely affect the characteristics of the electrochemical element in the electrochemical element. From the perspective of being relatively easy to plastically deform, it is preferred to use a foamed metal porous body [such as "Celmet (registered trademark)" manufactured by Sumitomo Electric Industries, Ltd.].

[0039] From the viewpoint of better ensuring its function, the thickness of the porous metal layer in the electrochemical element is preferably 100 μm or more, and more preferably 150 μm or more. In addition, there is no particular restriction on the upper limit of the thickness of the porous metal layer in the electrochemical element, but from the viewpoint of suppressing the volume of the components that do not participate in power generation in the outer casing, it is preferably 1500 μm or less, and more preferably 1000 μm or less.

[0040] The thickness of the porous metal layer is determined from the maximum value of the width in the thickness direction of an image of a cross section in the thickness direction observed at a magnification of 50 to 1000 times using a scanning electron microscope (SEM) (the values ​​in the examples described below are values ​​determined by these methods).

[0041] It should be noted that, as described above, the porous metal layer is preferably a porous body formed by compressing a metal porous body in the thickness direction, and its thickness is preferably 90% or less of the thickness of the metal porous body (the foamed metal porous body, etc.) used to constitute the porous metal layer, and more preferably 80% or less. Therefore, the thickness of the metal porous body (the foamed metal porous body, etc.) used to constitute the porous metal layer is preferably 150 to 1000 μm.

[0042] In addition, regarding the porosity of the metal porous body (such as the foamed metal porous body) used to form the porous metal layer, from the viewpoints of making the plastic deformation caused by pressing the electrode laminate easier, ensuring the reduction effect of the internal resistance of the electrochemical element more favorably, and suppressing the deviation thereof, it is preferably 99.5% or less, more preferably 99% or less, and still more preferably 98.5% or less. From the viewpoint of ensuring sufficient strength for use, it is preferably 80% or more, more preferably 90% or more, and still more preferably 95% or more.

[0043] In Figure 1 In the electrochemical element 10 shown, a porous metal layer 30 is disposed on the surface of the current collector 212 in the first electrode 21 on the side opposite to the electrode mixture layer 211. On the other hand, a lead wire 40 made of a metal foil or the like for electrically connecting the second electrode 22 to the conduction path 91 is disposed on the surface of the current collector 222 in the second electrode 22 on the side opposite to the electrode mixture layer 221. However, a porous metal layer may also be disposed between the current collector 221 of the second electrode 22 and the lead wire 40.

[0044] In addition, in Figure 1 In the electrochemical element 10 shown, a pressing unit 50 having a function of pressing the electrode laminate 20 against the porous metal layer 30 is provided between the lead wire 40 and the lid body 70. When the pressing unit 50 is provided, the current collector 212 of the first electrode 21 constituting the electrode laminate 20 is pressed against the porous metal layer 30 by its pressing force. Therefore, while the porous metal layer 30 is better plastically deformed, the current collector 212 and the porous metal layer 30 can be better contacted. Thereby, the effect of reducing the internal resistance of the electrochemical element and suppressing the deviation thereof is further improved by the pressing unit that presses the electrode laminate against the porous metal layer.

[0045] Examples of the pressing unit include a spacer made of an elastic body such as a rubber sheet or a spring (leaf spring, etc.).

[0046] In the method for manufacturing an electrode laminate according to the second aspect of the present invention, in an electrode laminate having a first electrode, a second electrode, and a separator layer interposed therebetween, at least one of the first electrode and the second electrode is configured to have an electrode mixture layer and a sheet-like current collector disposed on the surface of the electrode mixture layer, and the sheet-like current collector is formed by compressing a porous substrate in the thickness direction. Here, when the thickness of the porous substrate before compression is s, the thickness of the portion of the porous substrate opposite to the electrode mixture layer after compression is t, the thickness of the electrode mixture layer is a, and the thickness of the separator layer is b, the compression amount of the porous substrate is adjusted so as to satisfy s - t < a + b.

[0047] Figure 2 2 is a cross-sectional view schematically showing a main part of an example of an electrode stack produced by the production method of the present invention. Figure 2 The electrode stack shown includes a first electrode including an electrode mixture layer 111 and a sheet-like current collector 112 , a second electrode including an electrode mixture layer 121 , and a separator 130 interposed between the first electrode and the second electrode.

[0048] The sheet-like current collector 112 is formed by compressing the porous substrate in the thickness direction (downward direction in the figure) to a thickness of t, but a portion (the portion on the right side of the figure that is not opposite to the lower surface of the electrode mixture layer 111) is not compressed, and the thickness of this portion is maintained at the original thickness s of the porous substrate. At this time, when the front end of the uncompressed portion of the current collector 112 reaches the electrode mixture layer 121 of the second electrode, a short circuit occurs.

[0049] However, in the manufacturing method of the present invention, if Figure 2 As shown, the compression amount of the porous substrate is adjusted so that the difference "st" between the thickness s of the porous substrate before compression and the thickness t of the part of the porous substrate (collector 112) opposite to the electrode mixture layer 121 after compression is smaller than the sum "a+b" of the thickness a of the electrode mixture layer 111 and the thickness b of the isolation layer 130, thereby manufacturing an electrode stack.

[0050] It should be noted that when the porous substrate is compressed in the thickness direction, a part of the substrate is sometimes buried in the electrode mixture layer, and the electrode mixture enters the pores of the sheet-like current collector. However, in the present invention, the electrode mixture existing in the pores of the sheet-like current collector is excluded, and the part of the electrode mixture existing between the sheet-like current collector and the isolation layer is set to the thickness of the electrode mixture layer: a. In the case where a part of the substrate is buried in the electrode mixture layer, the counter electrode ( Figure 2 The front end of the second electrode) side is closer to the electrode mixture layer of the counter electrode, but the compression amount of the porous substrate is adjusted by determining the thickness of the electrode mixture layer as described above. Therefore, when the porous substrate is compressed to form a sheet-shaped current collector, even if the position of the porous substrate and the electrode mixture layer is offset and an insufficiently compressed portion is generated in a part of the porous substrate, the occurrence of internal short circuit in the electrochemical element caused by the contact between the portion and the counter electrode can be well suppressed.

[0051] In the electrode stack manufactured by the manufacturing method of the present invention, either the first electrode or the second electrode has the above-mentioned structure, that is, it has an electrode mixture layer and a sheet-like collector arranged on the surface of the electrode mixture layer. The sheet-like collector is a collector formed by compressing a porous substrate in the thickness direction. Both the first electrode and the second electrode may have the above-mentioned structure.

[0052] Here, in a case where the surfaces of the electrode mixture layers of the first electrode and the second electrode are respectively arranged on sheet-shaped collectors formed by compressing a porous substrate in the thickness direction, in order to prevent the collectors from contacting each other and causing a short circuit, it is preferred that in at least one electrode, the compression amount of the porous substrate is adjusted so that the value of st is less than a to form a sheet-shaped collector.

[0053] The electrochemical device in the second aspect of the present invention comprises an outer casing and the electrode stack of the present invention sealed inside the outer casing, and the electrode stack is an electrode stack produced by the production method of the present invention.

[0054] Figure 3 2 is a cross-sectional view schematically showing an example of the electrochemical device of the present invention having an electrode stack produced by the production method of the present invention. Figure 3 In the electrochemical element 100 shown, an electrode stack 140 having a first electrode 110, a second electrode 120, and a separator 130 interposed therebetween is enclosed in an outer casing formed of a metal outer can 150, a metal sealing can 160, and a resin gasket 170 interposed therebetween. The sealing can 160 is fitted into the opening of the outer can 150 via the gasket 170, and the opening end of the outer can 150 is tightened inwardly, whereby the gasket 170 abuts against the sealing can 160, thereby sealing the opening of the outer can 150 and forming a sealed structure inside the element.

[0055] When the electrode stack 140 has a solid electrolyte layer as the separator 130, for example, only the electrode stack 140 is sealed in the outer casing. On the other hand, when the electrode stack 140 has a separator as the separator 130, an electrolyte (not shown) is sealed in the outer casing together with the electrode stack 140.

[0056] The first electrode 110 includes an electrode mixture layer 111 and a sheet-shaped current collector 112 formed by compressing a porous substrate in the thickness direction. In addition, the second electrode 120 includes an electrode mixture layer 121 and a sheet-shaped current collector 122 formed by compressing a porous substrate in the thickness direction. Figure 2The electrochemical element 100 shown shows a state where the porous substrate is assembled without positional shift when compressed in the thickness direction, the porous substrate is compressed as a whole, and the sheet-shaped collector 112 in the first electrode 110 and the sheet-shaped collector 122 in the second electrode 120 are both well formed.

[0057] Figure 3 In the electrochemical element 100 shown, the metal outer can 150 forms a conduction path on the first electrode 110 side, and the end of the sheet-shaped current collector 112 exposed on the surface of the first electrode 110 contacts the inner surface of the outer can 150, thereby conducting the first electrode 110 and the outer can 150 (the conduction path formed by the outer can 150). In addition, the outer surface of the outer can 150 serves as an external terminal for electrically connecting the electrochemical element to an external device.

[0058] In addition, Figure 3 In the electrochemical element 100 shown, the metal sealing can 160 forms a conduction path on the second electrode 120 side, and the end of the sheet-shaped current collector 122 exposed on the surface of the second electrode 120 contacts the inner surface of the sealing can 160, thereby the second electrode 120 and the sealing can 160 (the conduction path formed by the sealing can 160) are connected. In addition, the outer surface of the sealing can 160 serves as an external terminal for electrically connecting the electrochemical element to an external device.

[0059] In the first and second modes of the present invention, the electrochemical element includes batteries, capacitors, etc. In the first and second modes of the present invention, when the electrochemical element is a battery, both primary batteries and secondary batteries are included, and in addition, batteries (all-solid batteries) having a solid electrolyte layer between the positive electrode and the negative electrode, and batteries (batteries other than all-solid batteries) having a separator between the positive electrode and the negative electrode and an electrolyte (non-aqueous electrolyte, aqueous electrolyte, and gel electrolyte obtained by gelling these electrolytes) containing a solvent are included. In the first and second modes of the present invention, when the electrochemical element is a capacitor, both include double-layer capacitors, lithium-ion capacitors, etc.

[0060] Hereinafter, the first aspect and the second aspect of the present invention will be collectively described with respect to the constituent elements of the electrochemical device.

[0061] <Electrode Laminate>

[0062] The electrode stack includes a first electrode, a second electrode, and a separator interposed therebetween.

[0063] In the first aspect of the present invention, the first electrode and the second electrode include, for example, an electrode composed of a molded body of an electrode mixture containing an electrode active material, and an electrode having the molded body as an electrode mixture layer on the surface of a current collector.

[0064] In the second aspect of the present invention, as described above, at least one of the first electrode and the second electrode includes an electrode mixture layer and a sheet-like current collector disposed on the surface thereof.

[0065] In the case where the electrochemical element using the electrode stack is a battery or a lithium ion capacitor, either the first electrode or the second electrode is a positive electrode, and the other is a negative electrode. In addition, in the case where the electrochemical element using the electrode stack is a double electric layer capacitor, the first electrode and the second electrode may use electrodes of the same structure. Hereinafter, the molded body of the positive electrode mixture is described as a "molded body of the positive electrode mixture", and the positive electrode mixture layer is described as a "positive electrode mixture layer".

[0066] When the electrochemical device is a battery and one of the first electrode and the second electrode is a positive electrode, the electrode mixture constituting the battery, that is, the positive electrode mixture, contains a positive electrode active material and the like.

[0067] When the electrode is the positive electrode of a primary battery, the positive electrode active material can be the same as the positive electrode active material used in the non-aqueous electrolyte primary battery, alkaline battery, manganese battery, etc., which are known in the past. Specifically, for example, manganese dioxide, lithium-containing manganese oxides [for example, LiMn3O6, composite oxides having the same crystal structure as manganese dioxide (β-type, γ-type, or a structure in which β-type and γ-type are mixed, etc.) and a Li content of 3.5% by mass or less, preferably 2% by mass or less, more preferably 1.5% by mass or less, and particularly preferably 1% by mass or less, etc.], Li a Ti 5 / 3 Lithium-containing composite oxides such as O4 (4 / 3≤a<7 / 3); vanadium oxides; niobium oxides; titanium oxides; sulfides such as iron disulfide; graphite fluoride; silver sulfides such as Ag2S; nickel oxides such as NiO2, etc.

[0068] When the electrode is a positive electrode of a secondary battery, the positive electrode active material may be the same as the positive electrode active material used in conventionally known non-aqueous electrolyte secondary batteries, alkaline secondary batteries, etc. Specifically, Li 1- x M r Mn 2-r O4 (wherein M is at least one element selected from the group consisting of Li, Na, K, B, Mg, Ca, Sr, Ba, Ti, V, Cr, Zr, Fe, Co, Ni, Cu, Zn, Al, Sn, Sb, In, Nb, Ta, Mo, W, Y, Ru and Rh, 0≤x≤1, 0≤r≤1) represented by a spinel lithium manganese composite oxide, Li r Mn (1-s-t) Ni s M t O(2-u) F v (where M is at least one element selected from the group consisting of Co, Mg, Al, B, Ti, V, Cr, Fe, Cu, Zn, Zr, Mo, Sn, Ca, Sr, and W, 0 ≤ r ≤ 1.2, 0 < s < 0.5, 0 ≤ t ≤ 0.5, u + v < 1, -0.1 ≤ u ≤ 0.2, 0 ≤ v ≤ 0.1) The layered compound represented, Li 1-x Co 1-r M r O2 (where M is at least one element selected from the group consisting of Al, Mg, Ti, V, Cr, Zr, Fe, Ni, Cu, Zn, Ga, Ge, Nb, Mo, Sn, Sb, and Ba, 0 ≤ x ≤ 1, 0 ≤ r ≤ 0.5) The lithium cobalt composite oxide represented, Li 1-x Ni 1-r M r O2 (where M is at least one element selected from the group consisting of Al, Mg, Ti, Zr, Fe, Co, Cu, Zn, Ga, Ge, Nb, Mo, Sn, Sb, and Ba, 0 ≤ x ≤ 1, 0 ≤ r ≤ 0.5) The lithium nickel composite oxide represented, Li 1+s-x M 1-r N r PO4F s (where M is at least one element selected from the group consisting of Fe, Mn, and Co and N is at least one element selected from the group consisting of Al, Mg, Ti, Zr, Ni, Cu, Zn, Ga, Ge, Nb, Mo, Sn, Sb, V, and Ba, 0 ≤ x ≤ 1, 0 ≤ r ≤ 0.5, 0 ≤ s ≤ 1) The olivine-type composite oxide represented, Li 2-x M 1- r N r P2O7 (where M is at least one element selected from the group consisting of Fe, Mn, and Co and N is at least one element selected from the group consisting of Al, Mg, Ti, Zr, Ni, Cu, Zn, Ga, Ge, Nb, Mo, Sn, Sb, V, and Ba, 0 ≤ x ≤ 2, 0 ≤ r ≤ 0.5) The pyrophosphate compound represented, nickel hydroxide, silver oxide, etc., and only one of them can be used, or two or more can be used in combination.

[0069] In the case where the electrochemical element is an all-solid secondary battery, the average particle size of the positive electrode active material is preferably 1 μm or more, more preferably 2 μm or more, and preferably 10 μm or less, more preferably 8 μm or less. It should be noted that the positive electrode active material can be a primary particle or a secondary particle formed by agglomeration of primary particles. If a positive electrode active material having an average particle size in the above range is used, the interface with the solid electrolyte contained in the positive electrode increases, so the output characteristics of the battery are further improved.

[0070] The average particle size of various particles (positive electrode active material, solid electrolyte, etc.) referred to in this specification refers to the value of the 50% diameter (D) in the cumulative fraction based on volume when the integrated volume is obtained from the smallest particle using a particle size distribution measuring device (Microtrac particle size distribution measuring device "HRA9320" manufactured by Nikkiso Co., Ltd., etc.). 50 ).

[0071] When the electrochemical device is an all-solid secondary battery, the positive electrode active material preferably has a reaction suppression layer on its surface for suppressing the reaction with the solid electrolyte contained in the positive electrode.

[0072] In the molded body (positive electrode mixture layer) of the positive electrode mixture, if the positive electrode active material is in direct contact with the solid electrolyte, the solid electrolyte is oxidized to form a resistance layer, and the ion conductivity in the molded body (positive electrode mixture layer) of the positive electrode mixture may be reduced. By providing a reaction inhibition layer that inhibits the reaction with the solid electrolyte on the surface of the positive electrode active material, direct contact between the positive electrode active material and the solid electrolyte is prevented, and the reduction in ion conductivity in the molded body (positive electrode mixture layer) of the positive electrode mixture caused by oxidation of the solid electrolyte can be suppressed.

[0073] The reaction inhibition layer can be composed of a material having ion conductivity and capable of inhibiting the reaction of the positive electrode active material with the solid electrolyte. As a material capable of constituting the reaction inhibition layer, for example, an oxide containing Li and at least one element selected from the group consisting of Nb, P, B, Si, Ge, Ti and Zr can be cited, and more specifically, Nb-containing oxides such as LiNbO3, Li3PO4, Li3BO3, Li4SiO4, Li4GeO4, LiTiO3, LiZrO3, Li2WO4, etc. can be cited. The reaction inhibition layer can contain only one of these oxides, or more than two, and further, a plurality of these oxides can also form a composite compound. Among these oxides, Nb-containing oxides are preferably used, and LiNbO3 is more preferably used.

[0074] The reaction suppression layer is preferably present on the surface in an amount of 0.1 to 1.0 parts by mass relative to 100 parts by mass of the positive electrode active material. Within this range, the reaction between the positive electrode active material and the solid electrolyte can be suppressed well.

[0075] Examples of a method for forming a reaction suppression layer on the surface of a positive electrode active material include a sol-gel method, a mechanofusion method, a CVD method, a PVD method, and an ALD method.

[0076] From the viewpoint of further increasing the energy density of the electrochemical device, the content of the positive electrode active material in the positive electrode mixture is preferably 60 to 98% by mass.

[0077] The positive electrode mixture may contain a conductive aid. As a specific example, carbon materials such as graphite (natural graphite, artificial graphite), graphene, carbon black, carbon nanofibers, and carbon nanotubes may be cited. It should be noted that, for example, when Ag2S is used as the active material, Ag with conductivity will be generated during the discharge reaction, so a conductive aid may not be contained. When a conductive aid is contained in the positive electrode mixture, when the content of the positive electrode active material is set to 100 parts by mass, its content is preferably more than 1.0 parts by mass, preferably less than 7.0 parts by mass, and more preferably less than 6.5 parts by mass.

[0078] In addition, the positive electrode mixture may contain a binder. As a specific example, fluororesins such as polyvinylidene fluoride (PVDF) may be cited. It should be noted that, for example, in the case where the positive electrode mixture contains a sulfide-based solid electrolyte (described later in detail), even if a binder is not used, the positive electrode mixture may not contain a binder when good formability can be ensured in forming a molded body (positive electrode mixture layer) of the positive electrode mixture.

[0079] In the positive electrode mixture, when a binder is required, its content is preferably 15% by mass or less, and preferably 0.5% by mass or more. On the other hand, in the positive electrode mixture, when formability can be obtained even without a binder, its content is preferably 0.5% by mass or less, more preferably 0.3% by mass or less, and further preferably 0% by mass (i.e., without a binder).

[0080] When the electrochemical device is an all-solid battery (all-solid primary battery, all-solid secondary battery), it is preferred that the positive electrode mixture contain a solid electrolyte.

[0081] The solid electrolyte contained in the positive electrode mixture is not particularly limited as long as it has lithium ion conductivity, and for example, a sulfide-based solid electrolyte, a hydride-based solid electrolyte, a halide-based solid electrolyte, an oxide-based solid electrolyte, etc. can be used.

[0082] As sulfide-based solid electrolytes, particles such as Li2S-P2S5, Li2S-SiS2, Li2S-P2S5-GeS2, and Li2S-B2S3-based glasses can be cited. In addition, thio-LISICON-type materials [Li 10 GeP2S 12 、Li 9.54 Si 1.74 P 1.44 S 11.7 Cl 0.3 etc., which have Li 12-12a-b+c+6d-e M 1 3+a-b-c- d M 2 b M 3 c M 4 d M 5 12-e X e (where M 1 is Si, Ge, or Sn, M 2 is P or V, M 3 is Al, Ga, Y, or Sb, M 4 is Zn, Ca, or Ba, M 5 is S, or S and O, X is F, Cl, Br, or I, 0 ≤ a < 3, 0 ≤ b + c + d ≤ 3, 0 ≤ e ≤ 3), and materials with a thiogermanate crystal structure.

[0083] As hydride-based solid electrolytes, for example, LiBH4, solid solutions of LiBH4 and the following alkali metal compounds (e.g., solid solutions with a molar ratio of LiBH4 to alkali metal compound of 1:1 to 20:1), etc. can be cited. As the alkali metal compounds in the solid solutions, at least one selected from the group consisting of lithium halides (LiI, LiBr, LiF, LiCl, etc.), rubidium halides (RbI, RbBr, RbF, RbCl, etc.), cesium halides (CsI, CsBr, CsF, CsCl, etc.), lithium amide, rubidium amide, and cesium amide can be cited.

[0084] As halide-based solid electrolytes, for example, monoclinic LiAlCl4, defective spinel-type or layered-structured LiInBr4, monoclinic Li 6-3m Y m X6 (where 0 < m < 2 and X = Cl or Br), etc. In addition, for example, known materials described in International Publication No. 2020 / 070958 and International Publication No. 2020 / 070955 can be used.

[0085] Examples of oxide-based solid electrolytes include garnet-type Li7La3Zr2O 12 、NASICON type Li 1+ O Al 1+O Ti 2-O (PO4)3、Li 1+p Al 1+p Ge 2-p (PO4)3, Perovskite-type Li 3q La 2 / 3-q TiO3, etc.

[0086] Among these solid electrolytes, sulfide-based solid electrolytes are preferred from the perspective of high lithium ion conductivity, and sulfide-based solid electrolytes containing Li and P are more preferred. From the perspective of higher lithium ion conductivity and high chemical stability, sulfide-based solid electrolytes having an argyrodite-type crystal structure are further preferred.

[0087] As a sulfide-based solid electrolyte having an argyrodite-type crystal structure, a substance represented by the following general composition formula (1) or the following general composition formula (2), such as Li6PS5Cl, is particularly preferred.

[0088] Li 7-x+y PS 6-x Cl x+y (1)

[0089] In the general composition formula (1), 0.05≤y≤0.9, -3.0x+1.8≤y≤-3.0x+5.7.

[0090] Li 7-a PS 6-a Cl b Br c (2)

[0091] In the general composition formula (2), a=b+c, 0 <a≤1.8、0.1≤b / c≤10.0。

[0092] From the viewpoint of reducing grain boundary resistance, the average particle size of the solid electrolyte is preferably 0.1 μm or more, more preferably 0.2 μm or more. On the other hand, from the viewpoint of forming a sufficient contact interface between the active material and the solid electrolyte, it is preferably 10 μm or less, more preferably 5 μm or less.

[0093] From the viewpoint of further improving the ionic conductivity in the positive electrode and further improving the output characteristics of the electrochemical element, when the content of the positive electrode active material is set to 100 parts by mass, the content of the solid electrolyte in the positive electrode mixture is preferably 10 parts by mass or more, more preferably 15 parts by mass or more. However, when the amount of solid electrolyte in the positive electrode mixture is too much, the amount of other components decreases, and the effect brought by them may become smaller. Thus, when the content of the positive electrode active material is set to 100 parts by mass, the content of the solid electrolyte in the positive electrode mixture is preferably 65 parts by mass or less, more preferably 60 parts by mass or less.

[0094] When the electrochemical element is a battery and one of the first electrode and the second electrode is a negative electrode, the electrode mixture constituting the battery, i.e., the negative electrode mixture, contains a negative electrode active material, etc. Hereinafter, the molded body of the negative electrode mixture is described as "the molded body of the negative electrode mixture", and the negative electrode mixture layer is described as "the negative electrode mixture layer".

[0095] As the negative electrode active material, for example, carbon materials such as graphite, lithium titanium oxide (lithium titanate, etc.), simple substances containing elements such as Si and Sn, compounds (oxides, etc.) and alloys thereof, etc. In addition, lithium metal and lithium alloys (lithium-aluminum alloys, lithium-indium alloys, etc.) can also be used as negative electrode active materials.

[0096] From the viewpoint of further increasing the energy density of the battery, the content of the negative electrode active material in the negative electrode mixture is preferably 40 to 99% by mass.

[0097] The negative electrode mixture may contain a conductive aid. As a specific example, the same conductive aid as the material that can be contained in the positive electrode mixture can be cited. When the content of the negative electrode active material is set to 100 parts by mass, the content of the conductive aid in the negative electrode mixture is preferably 10 to 30 parts by mass.

[0098] In addition, the negative electrode mixture may contain a binder. As a specific example, the same substance as the binder previously exemplified as a substance that can be contained in the positive electrode mixture can be cited. It should be noted that, for example, as in the case where the negative electrode mixture contains a sulfide-based solid electrolyte (described later), even if a binder is not used, the negative electrode mixture may not contain a binder if good formability can be ensured in forming a molded body (negative electrode mixture layer) of the negative electrode mixture.

[0099] In the negative electrode mixture, when a binder is required, its content is preferably 15% by mass or less, and preferably 0.5% by mass or more. On the other hand, in the negative electrode mixture, when formability can be obtained even without a binder, its content is preferably 0.5% by mass or less, more preferably 0.3% by mass or less, and further preferably 0% by mass (i.e., no binder).

[0100] In the case where the electrochemical element is an all-solid-state battery, it is preferred that a solid electrolyte be contained in the negative electrode mixture. As a specific example thereof, the same substance as the solid electrolyte previously exemplified as a substance that can be contained in the positive electrode mixture can be cited. Among the solid electrolytes exemplified above, it is preferred to use a sulfide-based solid electrolyte from the perspective of having high lithium ion conductivity and having the function of improving the formability of the negative electrode mixture, and it is more preferred to use a sulfide-based solid electrolyte having a argyrodite-type crystal structure, and it is further preferred to use a solid electrolyte represented by the composition formula (1) or the composition formula (2).

[0101] For the same reasons as in the case of the positive electrode mixture, the average particle size of the solid electrolyte in the negative electrode mixture is preferably 0.1 μm or more, more preferably 0.2 μm or more, and is preferably 10 μm or less, more preferably 5 μm or less.

[0102] From the viewpoint of further improving the ion conductivity in the negative electrode and further improving the output characteristics of the electrochemical element, when the content of the negative electrode active material is set to 100 parts by mass, the content of the solid electrolyte in the negative electrode mixture is preferably 30 parts by mass or more, more preferably 35 parts by mass or more. However, when the amount of solid electrolyte in the negative electrode mixture is too much, the amount of other components decreases, and the effect brought by them may become smaller. Thus, when the content of the negative electrode active material is set to 100 parts by mass, the content of the solid electrolyte in the negative electrode mixture is preferably 130 parts by mass or less, more preferably 110 parts by mass or less.

[0103] In the first aspect of the present invention, when the first electrode and the second electrode have a molded body of an electrode mixture, the thickness of the molded body of the electrode mixture is preferably 500 to 3000 μm.

[0104] In the first aspect of the present invention, when the first electrode and the second electrode have a current collector, the current collector may be a metal foil, a punched metal, a mesh, an expanded metal, a foamed metal, a carbon sheet, or the like.

[0105] In such a current collector, it is preferred to use a foamed metal porous body [such as "Celmet (registered trademark)" manufactured by Sumitomo Electric Industries, Ltd.] from the perspective of higher current collection efficiency. It is speculated that this is because, when the first electrode and the second electrode have a molded body of an electrode mixture, the surface of the molded body of the electrode mixture is relatively rough, and the surface of the current collector composed of the foamed metal porous body is also relatively rough, so a part of its surface enters the inner side from the surface of the molded body of the electrode mixture, and the contact area becomes larger.

[0106] The thickness of the current collector is preferably 30 μm to 100 μm.

[0107] In the first aspect of the present invention, when the electrochemical device is a battery, one of the first electrode and the second electrode used as the negative electrode may be a sheet of a metal functioning as a negative electrode active material, such as a lithium sheet or a lithium alloy sheet.

[0108] In the second embodiment of the present invention, when the electrode has a sheet-like current collector, the porous substrate used to form the sheet-like current collector uses a conductive substrate with a high porosity that is easily compressed, and preferably a foamed metal porous body. As a specific example of a foamed metal porous body, "Celmet (registered trademark)" of Sumitomo Electric Industries, Ltd. can be cited. In addition, woven fabrics, nonwoven fabrics, etc. composed of carbon fibers can also be preferably used. It should be noted that the thickness (thickness before being compressed) of such a porous substrate before being used for an electrode (electrode stack) is preferably more than 0.1 mm, more preferably more than 0.3 mm, and particularly preferably more than 0.5 mm. On the other hand, it is preferably less than 3 mm, more preferably less than 2 mm, and particularly preferably less than 1.5 mm.

[0109] In order to easily integrate the porous substrate and the electrode mixture layer in the process of pressurizing the porous substrate and the electrode mixture, the porosity of the porous substrate before compression is preferably 80% or more, more preferably 90% or more, and particularly preferably 95% or more. On the other hand, in order to increase the conductivity by making the amount of the substrate above a certain level, the porosity is preferably 99.5% or less, more preferably 99% or less, and particularly preferably 98.5% or less.

[0110] In the electrode of the structure, the thickness of the sheet-like collector (the thickness after the porous substrate is compressed) is preferably 10 μm or more, more preferably 20 μm or more, particularly preferably 30 μm or more, on the other hand, preferably 300 μm or less, more preferably 200 μm or less, particularly preferably 100 μm or less. In addition, the thickness of the electrode mixture layer is preferably 0.2 mm or more, more preferably 0.5 mm or more, particularly preferably 0.7 mm or more, on the other hand, preferably 2 mm or less, more preferably 1.7 mm or less, particularly preferably 1.5 mm or less.

[0111] At least a portion of the compressed sheet-shaped current collector may be buried in the electrode mixture layer and integrated with the electrode mixture layer.

[0112] In the second embodiment of the present invention, in the case where only either the first electrode or the second electrode in the electrode stack is an electrode having an electrode mixture layer and a sheet-shaped current collector formed by compressing a porous substrate in the thickness direction, the other electrode may be, for example, a molded body of the electrode mixture [an electrode consisting only of (particles, etc.), an electrode having a structure in which a molded body of the electrode mixture (electrode mixture layer) is formed on a current collector (a current collector other than a compressed product of a porous substrate such as a metal foil)], a lithium sheet, a lithium alloy sheet, or the like, a sheet of a metal functioning as a negative electrode active material (in the case where the electrochemical element is a battery and the electrode is its negative electrode), etc.

[0113] It should be noted that, in order to reduce the resistance when the electrode with the sheet-like collector formed by compressing the porous substrate contacts the conductive path, it is preferred that the end of the electrode (the surface of the electrode) is only composed of a sheet-like collector. That is, when the porous substrate is compressed in the thickness direction when manufacturing the electrode laminate described later, the pores at the end of the porous substrate are flattened and disappear, and it is preferred that only the porous substrate is exposed on the surface of the electrode. However, it is also possible to be a state in which a part of the pores at the end of the porous substrate is not flattened and is filled with an electrode mixture therein, and a part of the electrode mixture can also be exposed on the surface of the electrode together with the end of the porous substrate without causing a large impact on the contact resistance of the conductive path.

[0114] However, the greater the proportion of the electrode mixture exposed on the surface of the electrode (area ratio), the greater the contact resistance of the conductive path between the porous substrate and the electrochemical element. Therefore, it is preferred that the area of ​​the exposed electrode mixture be less than 50% of the electrode surface when viewed from above, more preferably less than 25%, further preferably less than 15%, and particularly preferably less than 10%.

[0115] In the electrode stack in the second embodiment of the present invention, as described above, sometimes at least a portion of the sheet-like collector is buried in the electrode mixture layer, but the thickness of the sheet-like collector and the thickness of the electrode mixture layer are respectively calculated based on the maximum values ​​of the widths in the thickness direction of the area where the sheet-like collector can be confirmed and the area where the electrode mixture can be confirmed (excluding the portion overlapping with the area where the sheet-like collector can be confirmed) in the image obtained by observing the cross-section in the thickness direction of the electrode using a scanning electron microscope (SEM) at a magnification of 50 to 1000 times (the values ​​in the embodiments described later are values ​​calculated by these methods).

[0116] When the electrochemical device using the electrode stack is an electric double layer capacitor, the first electrode and the second electrode may have an electrode mixture molded body (electrode mixture layer) formed of an electrode mixture having the same structure as the positive electrode mixture except that activated carbon is used as the active material.

[0117] In addition, when the electrochemical element using the electrode stack is a lithium ion capacitor, for one of the first electrode and the second electrode, an electrode with the same structure as the first electrode and the second electrode in the double-layer capacitor can be used as the positive electrode, and for the other electrode, an electrode with the same structure as the negative electrode in the battery can be used as the negative electrode.

[0118] In the electrode stack, the separator is interposed between the first electrode and the second electrode. However, in batteries and capacitors that do not use an electrolyte containing a solvent, such as an all-solid-state battery, a solid electrolyte layer is used as the separator.

[0119] Among the solid electrolytes constituting the solid electrolyte layer, specific examples thereof include the same substances as the solid electrolytes previously exemplified as substances that can be contained in the positive electrode mixture. Among the solid electrolytes exemplified above, it is preferred to use a sulfide-based solid electrolyte, more preferably a sulfide-based solid electrolyte having an argyrodite-type crystal structure, and further preferably a solid electrolyte represented by the composition formula (1) or the composition formula (2), from the perspective of high lithium ion conductivity and the function of improving formability.

[0120] The solid electrolyte layer may have a porous body such as a resin nonwoven fabric as a support.

[0121] The thickness of the solid electrolyte layer is preferably 10 μm to 200 μm.

[0122] In an electrode stack used in a battery or capacitor using an electrolyte containing a solvent, a separator is used as a separation layer interposed between a first electrode and a second electrode.

[0123] The separator is preferably one that has sufficient strength and can retain a large amount of electrolyte. From this viewpoint, a microporous film or nonwoven fabric made of polyethylene, polypropylene or ethylene-propylene copolymer having a thickness of 10 to 50 μm and an opening ratio of 30 to 70% is preferred.

[0124] The electrode stack can be manufactured, for example, as follows: using a first electrode and / or a second electrode formed by a molded body of an electrode mixture obtained by pressure molding the electrode mixture, or using a molded body of the electrode mixture formed on the surface of a current collector as an electrode mixture layer, or using a sheet of a metal that functions as a negative electrode active material as the first electrode or the second electrode, and arranging them on the surface of a separately molded solid electrolyte layer, a diaphragm, etc. In addition, for example, the electrode stack can also be manufactured according to the following steps: a solid electrolyte constituting a solid electrolyte layer is put into a mold, and a temporary molded body is formed by pressure molding, an electrode mixture constituting a first electrode (or a second electrode) is put into one side of the temporary molded body of the solid electrolyte and pressure molding is performed, the solid electrolyte is integrated with the temporary molded body of the first electrode (or the second electrode), and then an electrode mixture constituting a second electrode (or the first electrode) is put into the other side of the temporary molded body of the solid electrolyte and pressure molding is performed.

[0125] Furthermore, when forming the first electrode and the second electrode, a current collector may be placed on one side of the electrode mixture put into a mold, and the mixture may be press-molded to form the first electrode and the second electrode having the current collector.

[0126] In addition, in particular, in the second aspect of the present invention, when manufacturing the electrode stack, for example, the following first to third steps can be applied.

[0127] In the first step, the solid electrolyte is placed in a mold and pressure-molded. The surface pressure of the pressure-molding in the first step is preferably 30 MPa to 120 MPa, for example.

[0128] In the next second step, an electrode mixture is placed on the solid electrolyte press-formed in the first step, and the electrode mixture and the solid electrolyte are press-formed together to form a laminate of the solid electrolyte layer and the electrode mixture layer. The surface pressure of the press-forming in the second step is preferably 30 MPa to 500 MPa, for example.

[0129] Furthermore, the mold is turned over, and the electrode mixture of the other party is placed on the opposite side of the solid electrolyte layer and the electrode mixture layer, and the electrode mixture and the solid electrolyte layer are further pressurized by the pressurization in the third step to obtain an electrode laminate. In order to fully increase the density of the electrode mixture layer, the surface pressure during pressurization in the third step is, for example, preferably 800MPa or more, more preferably 1000MPa or more, and particularly preferably 1200MPa or more.

[0130] The upper limit of the surface pressure during pressurization in the third step is not particularly specified, but in a general pressurizing device, the upper limit is usually about 2000 MPa.

[0131] Next, while the electrode laminate is laminated with the porous substrate, it is pressed in the thickness direction to compress the porous substrate, whereby an electrode laminate in which a sheet-like current collector is disposed on the surface of the electrode mixture layer of one electrode can be obtained. In this step, the porous substrate is compressed in the thickness direction. As the degree of compression, from the viewpoint of making the electrode mixture layer more reliable, specifically, it is preferable that the thickness of the compressed sheet-like current collector is 30% or less of the thickness of the porous substrate before compression, more preferably 20% or less, and particularly preferably 10% or less.

[0132] On the other hand, the lower limit value of the thickness of the compressed sheet-like current collector is determined within the range satisfying s - t < a + b. Specifically, it is preferable that the thickness of the compressed sheet-like current collector is 1% or more of the thickness of the porous substrate before compression, more preferably 2% or more.

[0133] In the case of manufacturing an electrode laminate having a separator, two electrodes obtained by pressing as described above can be prepared, and they can be disposed on both sides of the separator to form an electrode laminate. Further, by laminating this electrode laminate with a porous substrate and pressing it in the thickness direction, an electrode laminate in which a sheet-like current collector is disposed on the surface can be obtained. In addition, the electrode disposed on one side of the separator can be an electrode other than the above-described electrode (an electrode composed only of a molded body of an electrode mixture without a current collector, an electrode using a metal foil as a current collector, etc.).

[0134] <Outer package>

[0135] In the first aspect of the present invention, the outer package of the electrochemical element only needs to have a conduction path leading from the inside of the outer package to the outside, and the porous metal substrate on the surface of the electrode of the electrode laminate is in contact with the conduction path, so that the electrode and the conduction path can be electrically connected. For example, it can be used Figure 1 The outer package shown, which is composed of a housing having an outer package container and a lid. In such an outer package, the outer package container can be a container made of ceramic or resin. In addition, the lid can be a lid made of ceramic, resin, metal (iron-based alloys such as iron-nickel alloy, iron-nickel-cobalt alloy, etc.).

[0136] In the outer package container, the external terminal and the conduction path connecting the electrode of the electrode laminate to the external terminal can be made of metals such as manganese, cobalt, nickel, copper, molybdenum, silver, palladium, tungsten, platinum, gold, and alloys containing them.

[0137] In addition to being able to seal the outer container and the cover body by bonding them together with an adhesive, when a metal cover body is used, the cover body side of the side wall of the recessed portion of the outer container can also be made of metal (iron-nickel alloy, iron-nickel-cobalt alloy or other iron-based alloys, etc.) and sealed by welding it to the cover body.

[0138] In the second aspect of the present invention, the outer casing of the electrochemical element is made of, for example, Figure 3 The outer casing shown is composed of a case having an outer can and a sealing can. That is, the electrochemical element having such a case as an outer casing is coin-shaped (button-shaped).

[0139] When the outer package of the electrochemical element is a casing having an outer can and a sealing can, Figure 3 As shown, a case in which an outer can and a sealing can are sealed by caulking with a gasket interposed therebetween can be cited, and a case in which an outer can and a sealing can are bonded with a resin can also be cited as an example.

[0140] The outer can and the sealing can can be made of stainless steel, etc. In addition, in addition to polypropylene, nylon, etc., the raw material of the gasket can also be used. When heat resistance is required in relation to the use of the electrochemical element, a heat-resistant resin with a melting point exceeding 240°C can also be used. As the above-mentioned heat-resistant resin, fluororesin (tetrafluoroethylene-perfluoroalkoxyethylene copolymer (PFA) etc.), polyphenylene ether (PPE), polysulfone (PSF), polyarylate (PAR), polyethersulfone (PES), polyphenylene sulfide (PPS), polyetheretherketone (PEEK), etc. In addition, when the electrochemical element is used for a purpose requiring heat resistance, its seal can also be sealed with glass airtightness.

[0141] It should be noted that in the second embodiment of the present invention, the outer casing of the electrochemical element is not limited to an outer casing having an outer can and a sealing can as long as it has a conductive path from the inside of the outer casing to the outside, and the sheet-like current collector on the surface of the electrode of the electrode stack is in contact with the conductive path, so that the electrode and the conductive path can be electrically connected. For example, a ceramic shell, that is, a shell having a conductive path composed of a metal such as gold, platinum, silver, palladium, copper, nickel, cobalt, or an alloy thereof provided in a manner penetrating the constituent material (such as Figure 1 As shown in the figure, a casing having an outer container and a cover body is used as an outer casing of the electrochemical element.

[0142] The shape of the outer casing of the electrochemical device in plan view may be circular or may be a polygon such as a quadrilateral (square, rectangle).

[0143] <Electrolytes>

[0144] In the case of an electrochemical element having an electrode stack with a diaphragm as a separator, an electrolyte is used as described above. The electrolyte generally uses a liquid electrolyte (non-aqueous electrolyte or aqueous electrolyte) having a non-aqueous solvent or an aqueous solvent. Moreover, as the non-aqueous electrolyte, a non-aqueous electrolyte in which an electrolyte salt such as a lithium salt is dissolved in an organic solvent is used. As the organic solvent, there is no particular limitation, and examples thereof include chain esters such as dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, and methyl propyl carbonate; cyclic esters with high dielectric constants such as ethylene carbonate, propylene carbonate, butylene carbonate, and vinylene carbonate; mixed solvents of chain esters and cyclic esters, etc., and mixed solvents of chain esters as the main solvent and cyclic esters are particularly suitable.

[0145] As the electrolyte salt dissolved in the organic solvent when preparing the non-aqueous electrolyte, for example, when the electrochemical element is a battery or a lithium ion capacitor, LiPF6, LiBF4, LiAsF6, LiSbF6, LiCF3SO3, LiC4F9SO3, LiCF3CO2, Li2C2F4(SO3)2, LiC n F 2n+1 SO3 (n ≥ 2), LiN (RfSO2) (Rf'SO2), LiC (RfSO2) 3, LiN (RfOSO2) 2 [wherein Rf and Rf' are fluoroalkyl groups], etc. are used alone or in combination of two or more. In addition, when the electrochemical element is a double-layer capacitor, the electrolyte salt of the non-aqueous electrolyte solution uses (C2H5) 4NBF4, (C2H5) 4PBF4, etc.

[0146] The concentration of the electrolyte salt in the electrolytic solution is not particularly limited, but is preferably 0.3 mol / l or more, more preferably 0.4 mol / l or more, and is preferably 1.7 mol / l or less, more preferably 1.5 mol / l or less.

[0147] As the aqueous electrolyte, an alkaline aqueous solution (alkaline electrolyte) composed of an aqueous solution of an alkali metal hydroxide such as potassium hydroxide, sodium hydroxide, or lithium hydroxide, an aqueous solution having a pH in the range of 3 to 12, or the like is used.

[0148] The concentration of the hydroxide of the alkali metal in the alkaline electrolyte can be, for example, 25 to 40% by mass.

[0149] In addition, as an aqueous solution having a pH in the range of from 3 to 12, a solution prepared by dissolving in water one or more of chlorides such as sodium chloride, potassium chloride, magnesium chloride, calcium chloride, ammonium chloride, and zinc chloride; hydroxides of alkali metals and alkaline earth metals (sodium hydroxide, potassium hydroxide, magnesium hydroxide, etc.), acetates (sodium acetate, potassium acetate, magnesium acetate, etc.), nitrates (sodium nitrate, potassium nitrate, magnesium nitrate, etc.), sulfates (sodium sulfate, potassium sulfate, magnesium sulfate, etc.), phosphates (sodium phosphate, potassium phosphate, magnesium phosphate, etc.), borates (sodium borate, potassium borate, magnesium borate, etc.), citrates (sodium citrate, potassium citrate, magnesium citrate, etc.), glutamates (sodium glutamate, potassium glutamate, magnesium glutamate, etc.); alkali metal bicarbonates (sodium bicarbonate, potassium bicarbonate, etc.); alkali metal percarbonates (sodium percarbonate, potassium percarbonate, etc.); halogen-containing compounds such as fluorides; and electrolyte salts such as polycarboxylic acids.

[0150] The electrolyte of the electrochemical element may be a gel electrolyte obtained by gelling the electrolytic solution with a gelling agent composed of a polymer or the like.

[0151] Example

[0152] Hereinafter, the present invention will be described in detail based on examples. However, the following examples do not limit the present invention.

[0153] (Example 1)

[0154] The average particle size of lithium titanate (Li4Ti5O 12 , negative electrode active material), a sulfide-based solid electrolyte (Li6PS5Cl) with an average particle size of 0.7 μm, and graphene (conductive aid) were mixed in a mass ratio of 50:41:9 to prepare a negative electrode mixture.

[0155] In addition, LiCoO2 (positive electrode active material) with an average particle size of 5 μm and a coating layer of LiNbO3 formed on the surface, a sulfide-based solid electrolyte (Li6PS5Cl) with an average particle size of 0.7 μm, and graphene are mixed in a mass ratio of 65:30.7:4.3 to prepare a positive electrode mixture.

[0156] Next, a powder of a sulfide-based solid electrolyte (Li6PS5Cl) with an average particle size of 0.7 μm is placed in a powder molding mold and pressure-molded using a press to form a temporary molding layer of a solid electrolyte layer. Furthermore, the negative electrode mixture is arranged on the upper surface of the temporary molding layer of the solid electrolyte layer and pressure-molded, and a temporary molding layer of a negative electrode is further formed on the temporary molding layer of the solid electrolyte layer.

[0157] Next, a porous body (thickness: 1.2 mm, porosity: 98%) obtained by cutting a nickel foamed metal porous body [nickel "Celmet" (registered trademark)] made by Sumitomo Electric Industries, Ltd. into a porous body with a diameter of 7.25 mm is placed on the temporary molded layer of the negative electrode formed on the temporary molded layer of the solid electrolyte layer and press-molded to form an integrated product of the solid electrolyte layer and the negative electrode.

[0158] Then, after the mold is turned upside down, the positive electrode mixture is placed on the upper surface of the solid electrolyte layer in the mold (the side opposite to the surface having the negative electrode) and pressure-molded to form a temporary molded layer of the positive electrode on the solid electrolyte layer.

[0159] Next, a porous body obtained by cutting a nickel foamed metal porous body similar to the porous body used in the negative electrode was placed on the temporary molded layer of the positive electrode formed on the solid electrolyte layer and pressure-molded to obtain an electrode laminate.

[0160] In having Figure 1 The structure shown in the figure has the same cross-sectional structure, the part of the cover body side of the side wall of the recess is made of iron-nickel-cobalt alloy, and the other part is made of ceramic. The bottom of the recess of the outer container is placed with a porous body made of nickel foamed metal porous body cut into a diameter of 7.25 mm, which is the same as the porous body used in the positive electrode and the negative electrode. The electrode stack is placed on it with the positive electrode as the lower side, and the remaining one sheet of the collector is placed on the negative electrode of the electrode stack. Then, a lead (Ni foil) is placed, and a rubber sheet (spacer) with a thickness of 400 μm is placed on it. Then, the side wall of the recess of the outer container is covered with a cover body made of iron-nickel-cobalt alloy, the rubber sheet is compressed in the thickness direction, and the cover body and the outer container are welded, thereby sealing the outer body composed of the outer container and the cover body to obtain a fully solid secondary battery. In the obtained all-solid secondary battery, the rubber sheet as a separator was compressed in the thickness direction, whereby the electrode stack pressed the porous metal layer composed of the foamed metal porous body. The thickness of the porous metal layer in the all-solid secondary battery was 200 μm.

[0161] (Comparative Example 1)

[0162] An all-solid secondary battery was produced in the same manner as in Example, except that the nickel foamed porous metal body placed in the bottom of the recessed portion of the outer container was replaced with a nickel foil (thickness: 200 μm).

[0163] (Comparative Example 2)

[0164] No nickel foamed metal porous body is used in the collector, and an electrode stack consisting only of a positive electrode, a solid electrolyte layer, and a negative electrode is produced by the same press molding. A graphite sheet (thickness: 200 μm) cut into a diameter of 7.25 mm is placed at the bottom of the recessed portion of the same outer container as in the embodiment, and the electrode stack is arranged thereon with the positive electrode at the bottom. The graphite sheet cut in the same manner is then placed on the negative electrode of the electrode stack, and then leads and rubber sheets (spacers) are placed in the same manner as in the embodiment, and sealed to produce an all-solid secondary battery.

[0165] As described above, 20 all-solid secondary batteries of the embodiments and comparative examples were prepared, and the internal resistance at 1 kHz was measured to find the average value and standard deviation. The results are shown in Table 1. It should be noted that, as shown in Table 1, the values ​​in brackets in the "Standard Deviation" column are coefficients of variation (values ​​expressed as percentages).

[0166] [Table 1]

[0167]

[0168] In the all-solid battery of Example 1 in which a porous metal layer is arranged on the bottom surface of a concave container, the value of internal resistance is low, and the deviation of the value is small and stable. On the other hand, the battery of Comparative Example 1 in which a metal foil is arranged on the bottom surface of a concave container instead of a porous metal layer, and the battery of Comparative Example 2 in which a graphite sheet is used as a collector, have a high value of internal resistance and a large deviation of the value compared with the battery of Example 1. In particular, in the battery of Comparative Example 1, the deviation is large, and there is a case where the internal resistance cannot be measured due to the inability to conduct electricity, so in Table 1, in addition to these, the average value and the standard deviation are shown.

[0169] (Example 2)

[0170] The average particle size of lithium titanate (Li4Ti5O 12 , negative electrode active material), a sulfide-based solid electrolyte (Li6PS5Cl) with an average particle size of 0.7 μm, and graphene (conductive aid) were mixed in a mass ratio of 50:41:9 to prepare a negative electrode mixture.

[0171] In addition, LiCoO2 (positive electrode active material) with an average particle size of 5 μm and a coating layer of LiNbO3 formed on the surface, a sulfide-based solid electrolyte (Li6PS5Cl) with an average particle size of 0.7 μm, and graphene are mixed in a mass ratio of 65:30.7:4.3 to prepare a positive electrode mixture.

[0172] Next, a powder of a sulfide-based solid electrolyte (Li6PS5Cl) with an average particle size of 0.7 μm was placed in a powder molding mold, and a press was used to perform pressure molding at a surface pressure of 70 MPa to form a temporary molding layer of the solid electrolyte layer. Furthermore, the negative electrode mixture was arranged on the upper surface of the temporary molding layer of the solid electrolyte layer, and pressure molding was performed at a surface pressure of 50 MPa to further form a temporary molding layer of the negative electrode on the temporary molding layer of the solid electrolyte layer.

[0173] Furthermore, after turning the mold upside down, the positive electrode mixture is arranged on the upper surface of the solid electrolyte layer in the mold (the opposite side of the surface with the negative electrode), and pressure molding is performed at a surface pressure of 1400 MPa to obtain an electrode stack with thicknesses of 0.8 mm, 0.35 mm and 1.4 mm for the positive electrode, solid electrolyte layer and negative electrode, respectively.

[0174] Next, a flexible graphite sheet "PERMA-FOIL (product name)" (thickness: 0.1 mm, apparent density: 1.1 g / cm 3 ) and nickel-made foamed metal porous body of Sumitomo Electric Industries [nickel-made "Celmet" (registered trademark), thickness: 1.2 mm, porosity: 98%) are punched out into the same size as the electrode stack. On the inner bottom surface of a stainless steel sealing can embedded with a polypropylene annular gasket, the flexible graphite sheet, the electrode stack and the foamed metal porous body are stacked in sequence, and then, after covering with a stainless steel outer can, the open end of the outer can is caulked inward to seal, thereby making a flat all-solid battery. It should be noted that the electrode stack is placed in a manner in which the negative electrode is located on the side of the flexible graphite sheet (sealing can side) and the positive electrode is located on the side of the foamed metal porous body (outer can side). In addition, assuming that the position of the foamed metal porous body is offset during assembly, the battery is assembled in a manner in which the foamed metal porous body is in an offset position relative to the electrode stack.

[0175] In the battery, when the open end of the outer can is caulked, the foamed metal porous body is compressed in the thickness direction, thereby forming a positive electrode having a sheet-like current collector on the surface of the positive electrode mixture layer.

[0176] The sealed battery was disassembled and the thickness of the sheet-shaped collector opposite to the positive electrode mixture layer after compression was investigated. The result was 0.1 mm, which was different from the thickness of the porous substrate before compression (1.2 mm). 1.1 mm was smaller than the sum of the thickness of the positive electrode mixture layer (0.8 mm) and the thickness of the solid electrolyte layer (0.35 mm): 1.15 mm.

[0177] The 100 assembled batteries were charged and discharged to investigate whether there were short circuits, but no short circuits were confirmed.

[0178] For comparison, an electrode stack was prepared in which the thicknesses of the positive electrode, solid electrolyte layer, and negative electrode were set to 0.7 mm, 0.3 mm, and 1.2 mm, respectively. Four of the flexible graphite sheets were overlapped on the negative electrode side. The porous substrate was replaced with a foamed metal porous body with a thickness of 1.4 mm before compression. Apart from this, a flat all-solid-state battery was prepared in the same manner as the above-mentioned battery.

[0179] The sealed battery was disassembled and the thickness of the sheet-shaped collector relative to the positive electrode mixture layer after compression was investigated. The result was 0.12 mm, which was different from the thickness of the porous substrate before compression (1.4 mm): 1.28 mm, which was greater than the sum of the thickness of the positive electrode mixture layer (0.7 mm) and the thickness of the solid electrolyte layer (0.3 mm): 1 mm.

[0180] The 100 assembled batteries were charged and discharged to check for short circuits, and it was found that 8 batteries had short circuits.

[0181] From the above results, it was confirmed that when a porous substrate is compressed in the thickness direction to form a sheet-shaped current collector, by adjusting the compression amount of the porous substrate, even if positional displacement of the porous substrate occurs, short circuit can be prevented from occurring.

[0182] The present invention can also be implemented in other ways than those described above without departing from the scope of its purpose. The embodiments disclosed in this application are examples, and the present invention is not limited to these embodiments. The scope of the present invention is interpreted in priority to the records of the attached claims compared to the description of the specification, and all changes within the scope equivalent to the claims are included in the claims.

[0183] Possibility of Industrial Application

[0184] The electrochemical device of the present invention can be used in the same applications as conventionally known electrochemical devices. In addition, the electrode stack produced by the production method of the present invention can constitute the electrochemical device of the second embodiment of the present invention.

[0185] Description of Reference Numerals

[0186] 10 electrochemical element; 20 electrode stack; 21 first electrode; 211 electrode mixture layer (molded body of electrode mixture); 212 current collector; 22 second electrode; 221 electrode mixture layer (molded body of electrode mixture); 222 current collector; 23 separator; 30 porous metal layer; 40 lead; 50 pressing unit (spacer); 80, 90 external terminal; 81, 91 conductive path; 100 electrochemical element; 110 first electrode; 111 electrode mixture layer; 112 sheet-shaped current collector; 120 second electrode; 121 electrode mixture layer; 122 sheet-shaped current collector; 130 separator; 140 electrode stack; 150 outer can; 160 sealing can; 170 gasket.

Claims

1. An electrochemical element, characterized in that: Comprising: An electrode laminate having a first electrode, a second electrode, and a separator layer interposed between the first electrode and the second electrode, and An exterior body that seals the electrode laminate therein; At least one of the first electrode and the second electrode of the electrode laminate has a current collector on the surface opposite to the separator layer and is electrically connected to a porous metal layer disposed on the surface of the current collector; The electrochemical element has a pressing unit that presses the electrode laminate against the porous metal layer; The exterior body has a conduction path leading from the inside to the outside, and the conduction path is electrically connected to the porous metal layer.

2. The electrochemical element according to claim 1, wherein the porous metal layer is formed of a foamed metal porous body.

3. The electrochemical element according to claim 1, wherein the separator layer is a solid electrolyte layer.

4. A method for manufacturing an electrode laminate, which is a method for manufacturing an electrode laminate having a first electrode, a second electrode, and a separator layer interposed therebetween, characterized in that At least one of the first electrode and the second electrode has an electrode binder layer and a sheet-like current collector disposed on the surface of the electrode binder layer, The manufacturing method includes a step of compressing a porous substrate in the thickness direction to form the sheet-like current collector, When the thickness of the porous substrate before compression is s, the thickness of the compressed portion of the porous substrate facing the electrode binder layer is t, the thickness of the electrode binder layer is a, and the thickness of the separator layer is b, the compression amount of the porous substrate is adjusted so as to satisfy s - t < a + b.

5. The method for manufacturing an electrode laminate according to claim 4, wherein the porous substrate is a foamed metal porous body.

6. The method for manufacturing an electrode laminate according to claim 4, wherein the separator layer is a solid electrolyte layer.

7. An electrochemical element, characterized in that: Having an exterior body and an electrode laminate sealed inside the exterior body, The electrode laminate is an electrode laminate manufactured by the method for manufacturing an electrode laminate according to any one of claims 4 to 6.

8. A method for manufacturing an electrochemical element, characterized in that: A method for manufacturing an electrochemical element having an exterior body and an electrode laminate sealed inside the exterior body, As the electrode laminate, an electrode laminate manufactured by the method for manufacturing an electrode laminate according to any one of claims 4 to 6 is used.

Citation Information

Patent Citations

  • Flat solid-state battery and method for manufacturing same

    WO2020066323A1

  • Halide solid electrolyte material and battery using same

    WO2020070955A1

  • Halide solid electrolyte material and battery using same

    WO2020070958A1